Firing Behavior and Network Activity of Single Neurons in Human Epileptic Hypothalamic Hamartoma - Steinmetz, Peter N.; Wait, Scott D.; Lekovic, Gregory P.; Rekate, Harold L.; Kerrigan, John F. (Frontiers in Neurology, 2013)
Objective: Human hypothalamic hamartomas (HH) are intrinsically epileptogenic and are associated with treatment-resistant gelastic seizures. The basic cellular mechanisms responsible for seizure onset within HH are unknown. We used intra-operative microwire recordings of single neuron activity to measure the spontaneous firing rate of neurons and the degree of functional connection between neurons within the tumor. Technique: Fourteen patients underwent transventricular endoscopic resection of HH for treatment-resistant epilepsy. Prior to surgical resection, single neuron recordings from bundled microwires (total of 9 contacts) were obtained from HH tissue. Spontaneous activity was recorded for two or three 5-minute epochs under steady-state general anesthesia. Off-line analysis included cluster analysis of single unit activity and probability analysis of firing relationships between pairs of neurons. Results: Altogether, 222 neurons were identified (mean 6 neurons per recording epoch). Cluster analysis of single neuron firing utilizing a mixture of Gaussians model identified two distinct populations on the basis of firing rate (median firing frequency 0.6 versus 15.0 spikes per second; p<10-5). Cluster analysis identified three populations determined by levels of burst-firing (median burst indices of 0.015, 0.18, and 0.39; p<10-15). Unbiased analysis of spontaneous single unit behavior showed that 51% of all possible neuron pairs within each recording epoch had a significant level of firing synchrony (p<10-15). The subgroup of neurons with higher median firing frequencies was more likely to demonstrate synchronous firing (p<10-7). Conclusions: HH tissue in-vivo contains neurons which fire spontaneously. The activity of single neurons is diverse but distributes into at least two electrophysiological phenoytpes. Functional linkage between single neurons suggests that HH neurons exist within local networks that may contribute to ictogenesis.